The Trisection of an Arbitrary Angle: A Condensed Classical Geometric Solution (JOURNAL OF ADVANCES IN MATHEMATICS, 2019)
This paper presents a short version of an elegant geometric solution of angle trisection that was published by this author on 2018-04-30 in Volume:  14 Issue:  02 of the Journal of Advances in Mathematics.The style of writing for the above paper was based on how teaching geometry was taught in high schools from 1940 to 1942.  Proofs of a problem consisted of a statement that was followed by a valid reason why the statement was made.  If the proof was many lines in length, the teacher wanted the students to show each step.  The students were not allowed to skip a step or steps to reach the final line of the proof.This short version was generated when a copy of the above paper was reviewed by a retired school teacher, who suggested the proof of the trisection of an arbitrary angle could be shortened.The exposed methods of proof have not changed from the Euclidean postulates of classical geometry.